Analysis of Financial Management Information Systems in Improving Performance at the Office of the Sub-District Head of Jagong Jeget (Case study of the Office of the Head of Sub-District of Jagong Jeget) - Putria Nurjanah (Penerbit ADM Bengkulu, 2022)
Abstract A financial information system is an information system designed to provide information about money options for users throughout the company. The financial information system is part of the MIS which is used to solve corporate financial problems. In general, the financial information system has an income system consisting of a data processing subsystem supported by an internal audit subsystem that provides internal data and information. For large companies it usually has staff internal auditors. Like other subsystems, this system is also equipped with the financial intelligence subsystem, which collects information from the environment.